Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O.; Juvenile Collection (Library of Congress) (New York : Morrow, 1983)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
Keywords: Divorce; Parent and child; Schools; Letters; Imprints 20th century 1983